Analisis Literatur Dampak Teknologi terhadap Perkembangan Kognitif Siswa Sekolah - Tabitha Zahra; Avrila Aura Sayyidhina; Chelsea Rizky Valentine (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Based on literature research conducted over the past five years, from 2020 to 2024, this study aims to analyze the positive and negative impacts of technology use on students' cognitive development in schools. Digital technology plays a significant role in modern education, both in supporting students' critical thinking, creativity and conceptual understanding, and in introducing risks such as decreased concentration and digital dependency. The method used was a literature study that used a sample of literature covering various levels of education, from elementary school to higher education, using relevant articles and journals. The results of the analysis show that technology can accelerate the learning process and increase students' learning motivation if used appropriately and accompanied by the role of parents or teachers. However, excessive and unsupervised use can lead to cognitive, social and emotional impairment. Therefore, a balanced strategy for using technology is needed so that the benefits can be maximized and the negative impacts minimized.